Improving MSME Performance through Accounting Knowledge and Financial Reporting: Fintech as a Moderator - Irma Oktarina Safitri; Baldric Siregar; Rudy Badrudin (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2026)
The purpose of this study is to determine the perception of Micro, Small, and Medium Enterprises (MSMEs) in Sleman Regency regarding accounting and financial knowledge in preparing financial reports on MSMEs performance moderated by Financial Technology. Using primary data by distributing questionnaires via Google Form to MSMEs in Sleman Regency with a purposive sampling method. A total of 200 samples were obtained with the criteria of micro businesses in Sleman Regency, having run a business for at least six months, having received facilities from the Sleman Regency Cooperatives, Small and Medium Enterprises Office, and having implemented digital connection services with financial technology. The data were processed using Partial Least Square (PLS) 4. The results of the study indicate that accounting knowledge and the ability to prepare financial reports have a positive and significant effect on MSMEs performance. Fintech acts as a moderator that strengthens the relationship between accounting knowledge and MSMEs performance, but has not shown a significant moderating effect between the relationship financial report preparation ability and MSME performance.